2017
DOI: 10.1371/journal.pone.0175037
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cetacean vaginal folds yield insights into functionality

Abstract: Complex foldings of the vaginal wall are unique to some cetaceans and artiodactyls and are of unknown function(s). The patterns of vaginal length and cumulative vaginal fold length were assessed in relation to body length and to each other in a phylogenetic context to derive insights into functionality. The reproductive tracts of 59 female cetaceans (20 species, 6 families) were dissected. Phylogenetically-controlled reduced major axis regressions were used to establish a scaling trend for the female genitalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
(75 reference statements)
0
36
2
Order By: Relevance
“…; Orbach et al. ). The vaginal folds of cetaceans vary in number, thickness, positioning, shape, and size across species and appear to be under strong selection pressures because fold lengths are positively allometric with body size (Orbach et al.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…; Orbach et al. ). The vaginal folds of cetaceans vary in number, thickness, positioning, shape, and size across species and appear to be under strong selection pressures because fold lengths are positively allometric with body size (Orbach et al.…”
mentioning
confidence: 97%
“…; cetaceans, Orbach et al. ). Because female genital adaptations can be subtle, careful quantification of morphological attributes is critical to identify patterns and the underlying evolutionary drivers of variation (Brennan and Prum ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies of genital evolution have found it difficult to separate the effects of cryptic female choice and sexual conflict, and therefore, the relative importance of one compared to the other is difficult to gauge. For example, an analysis of vaginal morphology of 20 species of cetaceans revealed extensive diversification in vaginal fold size, number, positioning and shape (Orbach et al., ), although the functional role of these vaginal folds in sexual selection is not immediately clear (Figure ). Further studies have found evidence for both congruent (genitalia are complementary) and antagonistic (genitalia are combative) coevolution between male and female genitalia in marine mammals, hinting at roles for either Fisherian cryptic female choice or sexual conflict mechanisms (Orbach et al., ).…”
Section: Cryptic Female Choice and Sexual Conflictmentioning
confidence: 99%